CHRONIC RENAL FAILURE CHRONIC GLOMERULONEPHRITIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Kidney disease (CK) is a disease that occurs when the condition of the kidney deteriorates. As a result, people's lives become worse. Kidney disease affects one in ten people worldwide. This is one of the main reasons for high medical costs. In high-income countries, the cost of transplantation and dialysis is between 2% and 3% of the annual medical budget [1]. Chronic kidney failure makes it difficult for the body to remove excess fluid from the blood. Advanced kidney disease can cause dangerous levels of fluid, electrolytes, and waste products to accumulate in the body. This can lead to complications such as high blood pressure, anemia, bone weakness, and nerve damage.